Comorbidity of Infectious Diseases and Anxiety Disorders in Adults and Its Association with Quality of Life: A Community Study - Witthauer, Cornelia; Gloster, Andrew T.; Meyer, Andrea Hans; Goodwin, Renee D.; Lieb, Roselind (Frontiers in Public Health, 2014)
Objective: Infectious diseases and anxiety disorders are common and both are associated with substantial burden to individual, families and society. A better understanding of their association may be helpful in explicating possible etiological mechanisms related to both. The goal of the current study was to investigate the relationship between specific infectious diseases and anxiety disorders among adults in the community, and to examine whether the co-occurrence of the two is associated with poorer quality of life compared to subjects with one or neither condition. Methods: We used data from the 1998 German Mental Health survey with 4,181 subjects aged 18-65. Various infectious diseases (lifetime) and health-related quality of life were assessed via self-report questionnaires and anxiety disorders (past 12-months) were diagnosed using M-CIDI interviews; Logistic regression analyses were used to evaluate the association between infectious diseases and anxiety disorders; a linear model adjusted for sex was used to examine whether comorbidity of infectious diseases and anxiety disorders was associated with quality of life. Results: Whooping cough (OR=1.69, 95%CI=1.36-2.09), scarlet fever (OR=1.31, 95%CI=1.02–1.68) and diphtheria (OR=1.79, 95%CI=1.21–2.64) were associated with increased prevalence of any anxiety disorder. Subjects with both infectious diseases and anxiety disorders reported lower levels of both mental and physical quality of life, compared with subjects with only one or neither condition. Conclusions: Extending prior research, this study suggests a relationship between specific infectious diseases and anxiety disorders in an adult community sample. Research targeting etiological mechanisms related to the interplay between infectious diseases and anxiety disorders is warrented.